Analisis Jabatan Dalam Meningkatkan Tatakelola Kinerja Pada Dinas Tenaga Kerja Transmigrasi Dan Sosial Kabupaten Malang - SETYO WARDANI, WIWIT; WIASTONO, AGUS (JOURNAL KOPERASI DAN MANAJEMEN, 2024)
There are many inconsistencies between positions and officeholders. So that the performance of an organization is felt to be less than optimal. The location of the research carried out by researchers was the Transmigration and Social Workforce Service in Malang Regency. The researcher's aim in choosing this location is related to research activities in the work area of the Transmigration and Social Workforce Service in Malang Regency. The data analysis methods in this research are qualitative analysis and quantitative analysis. Based on the results of the research that has been carried out, the researchers in this research, namely by testing and analyzing job analysis, have a simultaneous influence on performance achievement at the Malang Regency Manpower, Transmigration, and Social Service, which can be concluded based on the results of data processing in the field and matching the results of data processing. By using SPSS, it was concluded that the job analysis had a simultaneous effect on performance achievement at the Malang Regency Manpower, Transmigration, and Social Service. Meanwhile, the results of the researcher's research in the discussion also reveal that there is a partial influence of job specifications on performance achievement within the Malang Regency Manpower, Transmigration, and Social Service. And the final result of this research is that, by assessing the suitability of the research results and discussion, it can be concluded that, from the results of the research that has been carried out, the author recommends that job specifications are more dominant in influencing employee performance increases compared to others. Job specifications are able to improve employee performance and are categorized as improving the performance of the civil service organization so that it is able to achieve program objectives as desired in the environment at the Malang Regency Social and Transmigration Manpower Service.